Advances and Challenges in Islet Transplantation: Islet Procurement Rates and Lessons Learned from Suboptimal Islet Transplantation. (22nd December 2011) - Plesner, Annette; Verchere, C. Bruce
Abstract : The initial step in successful islet transplantation is procurement of healthy donor islets. Given the limited number of donor pancreata selected for islet isolation and that islets from multiple donors are typically required to obtain insulin independence, it is critical to improve pancreas procurement rates and yield of islets for transplantation. Islets are delicate microorgans that are susceptible to apoptosis, hypoxia, and ischemia during isolation, culture, and the peritransplant period. Once the islets are engrafted, both prompt revascularization and protection from beta-cell death and graft rejection are key to secure long-term survival and function. To facilitate the engraftment of more robust islets suitable for combating the challenging isolation period and proinflammatory transplantation milieu, numerous approaches have been employed to prevent beta-cell dysfunction and death including immune modulation, prevention of apoptosis and hypoxia, as well as stimulation of growth factors, angiogenesis, and reinnervation. In addition to briefly discussing islet isolation procedures, procurement rates, and islet transplantation, the relevant literature pertaining to successful suboptimal islet transplantation is reviewed to provide insight into potential approaches to balance the limited supply of available donor islets.